Phillis : a poetry collection - Clarke, Alison, 1970- (Brave & brilliant series ;, 2020)
"These poems reach through time to tell the remarkable story of Phillis Wheatley, the first African-American woman to publish a book of poetry, and who did so while she was enslaved. Phillis Wheatley was the first African American to publish a book of poetry. In 1773, her book, Poems on Various Subjects, Religious and Moral, was published to international acclaim. Wheatley was presented In London as "the African genius," and her writing was published in New England and England alike. Phillis Wheatley's name was known in households throughout literate North America. Yet Phillis Wheatley was a slave. In Phillis, Alison Clarke reaches through time to tell the story of this remarkable woman. Through a series of poems and prose-poems, Clarke presents Wheatley's world with depth and liveliness, reimagining the past for a modern audience while bringing sensibility and passion to the story of Wheatley's life. Wheatley's story is told in first-person poetry that illuminates significant chapters of her life, capturing the brilliant heights of her writing career along with the inevitable, brutal injustices she faced as an enslaved Black person in North America. Interspersed with poems written from the viewpoint of others who were themselves inspired by Wheatley, this is a collection of poetry that celebrates the resilience and accomplishments of Black History in general and one remarkable woman in particular."--